(untitled) (British Journal of Global Ecology and Sustainable Development, 2022)
The region is integrated in the development of an economic mechanism for managing environmental conflictsanalysis approaches have been implemented. Tfinancial-economic, socio-legal, socio-political and administrative-state methods of collective regulation of the process of habitat use were analyzed.